Why do we have so many molecules and biodiversity but so few antiparasite medicines? (2018)
ABSTRACT: Natural products are isolated from biodiversity, that is, from plants, microorganisms, insects, and marine organisms; most of the biodiversity is found in about 10-12 countries located around the Equator. For a long time, people chose this option to alleviate diseases and the industry to discover new medicines; however, from the 70's onwards synthetic products have displaced them. Today there is a rebirth of natural products research and annually hundreds of new natural and synthetic bioactive molecules are reported in specialized journals. On the other hands, new drugs are continually required and especially there is a deficit of them to treat the so-called Neglected Diseases, which affect and threaten the health of billions of people in the world. These diseases paradoxically affect almost all megadiverse countries. Thus, the richest countries in biodiversity do not benefit from the use of natural products because research, development and production of new medicines are carried out in more technologically advanced countries. Why do we have so many molecules in biodiversity and journals but so few medicines? How could new antiparasite drugs be developed quickly and cheaply in the countries affected by Neglected Diseases? A feasible alternative is the Mining in Press, that is, the search of molecules in scientific literature. In this paper we analyze the reasons why these valuable substances have not become drugs and remain curiosities of laboratories and libraries, and the advantages of using this approach as a source of drugs or templates to other bioactive molecules.